The Role Of The Financial Services Authority In Setting The Interest Rate For Financial Technology Loans As Consumer Protection Of Financial Services - Sri Astutik; Irawan Soerodjo (Yuridika, 2023)
The development of modern business in the digital era in the services of non-bank financial institutions, which provides convenience and acceleration in services to consumers of financial services is Financial Technology. Peer-to-peer lending is a fintech product that provides loans to debtors at high interest rates. The maximum loan interest rate set by the Indonesian Joint Funding Fintech Association (AFPI) is 0.8% per day. This determination is very burdensome for the debtor as a consumer of financial services, so there needs to be protection and regulation by the authorized institution. This normative legal research aims to determine the role of the Financial Services Authority in determining the Financial Technology Loan Interest Rate as the Protection of Financial Services Consumers. The results of this study, that the role of the Financial Services Authority as an institution that has the authority to regulate and supervise bank and non-bank financial institutions, has issued Financial Services Authority Regulation no. 77/POJK.01/2016 concerning Information Technology-Based Lending and Borrowing Services. In the POJK, OJK does not set loan interest rates. Peer-to-peer fintech lending providers are encouraged to offer reasonable interest rates and are still within a reasonable range.